Rozwiązane

a)[1/3-(1/3)]^2-[1/2-(-1/2)]^2=
b)2^5+4^4*5+2*2^5=
c)[(-1/3)^2*6-4*(-1/2)^]=
d)(4-(-6)^2:(-2)^3]:(-1/2)^2=
e)9-1/3(-3)^2:(-1/6)=



Odpowiedź :

b) = 32 + 256 * 5 + 2 * 32 = 32 + 1280 + 64 = 1376

c) chyba potęgi brak pod koniec ale ok ;d
= [ 1/9 * 6 - 4 * ( - 1/2)^? ] = [1/9 * 6/1 - 4 * (-1/2) ^? ] = [ 2/3 - 4 * ...... ] :p

d) [ 4 - 36 : ( -8 ) ] : 1/4 = [ 4 - ( -4 ) ] : 1/4 = [ 4+4 ] : 1/4 = 8 : 1/4 = 8/1 : 1/4 = 8/1 * 4/1 = 32/1 = 32

e) 9 * 1/3 * 9 : ( - 1/6) = 9 - 1/3 * 9/1 : ( - 1/6) = 9 - 3/1 : ( -1/6 ) = 9 - 3/1 * (-1/6 ) = 9 - ( - 18/1 ) = 9 + 18 = 27

; ]